2022
DOI: 10.1080/14686996.2022.2076568
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional injectable hydrogel for effective promotion of cartilage regeneration and protection against osteoarthritis: combined chondroinductive, antioxidative and anti-inflammatory strategy

Abstract: The regeneration of the articular cartilage defects is characterized by the improvement in the quality of the repaired tissue and the reduction in the potential development of perifocal osteoarthritis (OA). Usually, the injection of dexamethasone (Dex) in the OA joints slows down the progression of inflammation and relieves pain. However, the anti-inflammatory Dex injected in the joint cavity is rapidly cleared, leading to a poor therapeutic effect. Multifunctional hydrogels with simultaneous chondrogenic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In addition, the higher the mass fraction of DMON@Cur particles added, the apparent viscosity of the slurry was slightly reduced, but the effect was not significant. Frequency scans ( Figure 6B ) of the slurries showed that the G′ values for all slurries remained essentially constant throughout the frequency range, indicating good crosslinking ( Dong et al, 2022 ). The addition of DMON@Cur carrier particles had little effect on the internal crosslinking mechanism of the slurries, which were stable and continuous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the higher the mass fraction of DMON@Cur particles added, the apparent viscosity of the slurry was slightly reduced, but the effect was not significant. Frequency scans ( Figure 6B ) of the slurries showed that the G′ values for all slurries remained essentially constant throughout the frequency range, indicating good crosslinking ( Dong et al, 2022 ). The addition of DMON@Cur carrier particles had little effect on the internal crosslinking mechanism of the slurries, which were stable and continuous.…”
Section: Resultsmentioning
confidence: 99%
“…The DMON synthesis was based on the previously published technique with certain modifications ( Dong et al, 2022 ). The following procedures were carried out in the dark to produce DMON@Cur powder.…”
Section: Methodsmentioning
confidence: 99%
“…The results show that compared with the traditional hydrothermal method, the use of microfluidic chips can quickly prepare miR-200c-3p@ZIF-8 with uniform particle size, small dispersion coefficient and high encapsulation rate, and is conducive to industrial expansion production. The miRNA release behaviors of miR-200c-3p@ZIF-8 in buffers with different pH values (pH = 7.4 mimicking normal physiological environment; pH = 6.4 mimicking inflammatory microenvironment; and pH = 5.5 mimicking endosome/lysosome environments) ( Luo et al, 2017 ; Cao et al, 2022 ; Dong et al, 2022 ) were subsequently evaluated by nanodrop spectrophotometer, while the standard curve of miR-200c-3p was presented in Fig. S10, ESI†.…”
Section: Discussionmentioning
confidence: 99%
“… ( a ) Properties and applications of hemostatic hydrogels prepared from different polymers [ 23 , 24 , 25 , 26 , 27 , 28 ]. Copyright 2019, 2021 Elsevier.…”
Section: Figurementioning
confidence: 99%